The risk factors for Group B Streptococcus colonization during pregnancy and influences of intrapartum antibiotic prophylaxis on maternal and neonatal outcomes - Chen, Xiaoli; Cao, Sijia; Fu, Xiaochun; Ni, Yan; Huang, Bixuan; Wu, Jiayin; Chen, Ling; Huang, Shuying; Cao, Jiali; Yu, Weiwei; Ye, Huiming (BMC pregnancy and childbirth, 2023)
Background Group B Streptococcus (GBS), also referred as Streptococcus agalactiae , is one of the leading causes of life-threatening invasive diseases such as bacteremia, meningitis, pneumonia and urinary tract infection in pregnant women and neonates. Rates of GBS colonization vary by regions, but large-sample studies on maternal GBS status are limited in southern China. As a result, the prevalence of GBS among pregnant women and its associated risk factors and the efficacy of intrapartum antibiotic prophylaxis (IAP) intervention in preventing adverse pregnancy and neonatal outcomes remain poorly understood in southern China. Methods To fill this gap, we retrospectively analyzed demographic and obstetrical data of pregnant women who have undergone GBS screening and delivered between 2016 and 2018 in Xiamen, China. A total of 43,822 pregnant women were enrolled and only a few GBS-positive women did not receive IAP administration. Possible risk factors for GBS colonization were assayed by univariate and multivariate logistic regression analysis. Generalized linear regression model was applicated to analyze whether IAP is one of the impact factors of the hospital length of stay of the target women. Results The overall GBS colonization rate was 13.47% (5902/43,822). Although women > 35 years old ( P = 0.0363) and women with diabetes mellitus (DM, P = 0.001) had a higher prevalence of GBS colonization, the interaction between ages and GBS colonization was not statistically significant in Logistic Regression analysis (adjusted OR = 1.0014; 95% CI, 0.9950, 1.0077). The rate of multiple births was significantly dropped in GBS-positive group than that of GBS-negative group ( P = 0.0145), with no significant difference in the rate of fetal reduction ( P = 0.3304). Additionally, the modes of delivery and the incidences of abortion, premature delivery, premature rupture of membranes, abnormal amniotic fluid and puerperal infection were not significantly different between the two groups. The hospitalization stays of the subjects were not influenced by GBS infection. As for neonatal outcomes, the cases of fetal death in maternal GBS-positive group did not statistically differ from that in maternal GBS-negative group. Conclusion Our data identified that pregnant women with DM are at high risk of GBS infection and IAP is highly effective in prevention of adverse pregnancy and neonatal outcomes. This stressed the necessity of universal screening of maternal GBS status and IAP administration to the target population in China, and women with DM should be considered as priorities.